Optimizing the Role of Bhabinkamtibmas in Raising Public Awareness to Prevent the Spread of Covid-19 at the Denpasar Police - I Made Adi Ramajaya (Indonesian Journal of Police Studies, 2021)
The social problem currently experienced by the Indonesian people is the COVID-19 pandemic. This has a major impact on people's lives, but the implementation of COVID-19 prevention by the community is considered to be lacking, marked by low awareness of health protocols, in this study the aim of this study was to explore and find facts that led to the non-optimal role of Bhabinkamtibmas in increasing public awareness to prevent the spread of the virus. COVID-19 in the Denpasar Police. In order to analyze the research results, Management Theory, Optimization Concept, Consciousness Concept, and Bhabinkamtibmas Concept are used. Data analysis in this study used the results of in-depth interviews and document data obtained from relevant sources. This research was conducted in the Denpasar Police Legal Area and focused on the role of Bhabinkamtibmas in increasing public awareness. Bhabinkamtibmas plays an important role in fostering the community in the police strategy in the preventive sector. In Denpasar City, the spread of COVID-19 continues to increase and there are still many people who violate health protocols. This is influenced by internal factors and external factors. Internal factors include human resources, budget, facilities and infrastructure. External factors are many people who are constrained in the economic field of the community. From the protocol violations committed by the community, it is assessed that the role of Bhabinkamtibmas is still not optimal.